Hubungan Kondisi Fisik Rumah dan Perilaku dengan Kejadian TB Paru di Wilayah Kerja Puskesmas Batu 10 Kota Tanjungpinang - Dani Imaduddin; Onny Setiani; Suhartono Suhartono (Jurnal Kesehatan Masyarakat (Undip), 2019)
Background : Indonesia is one of the five countries that have the highest tuberculosis cases in 2016. One of the factors that facilitates the spread of pulmonary tuberculosis is in terms of environment and behavior. This study aims to determine the relationship between the physical condition of the house and behavior with the incidence of pulmonary TB disease in the working area of Puskesmas Batu 10.Method : analytical survey method with case control design used in this study. The technique of collecting data is carried out by observation and interviews in each sample of 37 respondents conducted in January-April 2019. Analysis of data using univariate and bivariate using chi-square test to see the relationship and risk factors and each outcome variable.Result : there is a relationship between the practice of preventing pulmonary TB (pValue = 0,001 and OR = 15,231 CI 95% = 4,417 – 52,520) with the incidence of  pulmonary TB,  but there is no relationship between the type of wall, type of floor,  the area of ventilation, ceiling and occupancy density where the p value is > 0,05.Conclusion : prevention of poor  pulmonary TB practices is significantly associated and ia a risk factor for the incidence of pulmonary TB in the working area of Puskesmas Batu 10 in Tanjungpinang.